Thermosensitive chitosan hydrogel loaded with cell-derived nanovesicles for cutaneous wound healing - Ren, Jingfei (Nanyang Technological University, 2020)
Advanced wound care management remains a significant clinical challenge nowadays. Anomalies in normal wound healing phases and complications caused by various pathophysiological factors often result in chronicity of the reparative process and exert excess discomforts and burdens to patients. Efforts to develop effective therapies to treat hard-to-heal wound have readily presented stem cells as a promising agent, thanks to their renewal and regenerative potencies. With latest progresses in understanding the curative mechanism of stem cells, top-down methods to fabricate cell-derived nanovesicles (CDNs) are developed to mimic the critical paracrine functions of stem cells and achieve excellent reproducibility and scalability. The aim of this project is to develop a thermosensitive hydrogel dressing capable of in- situ gelation on human cutaneous wound sites, which can also house the stem cell derived nanovesicles in the hydrogel matrix for sustained release and treatment. By combining the conventional passive dressing with bioactive CDNs, the project proposes an integrated solution to address the wound healing challenge. Hydrogel was successfully synthesized through a physical-crosslinking mechanism using chitosan, β-Glycerophosphate(βGP)/αβ-Glycerophosphate(αβGP) and sodium hydrogen carbonate (SHC). The resultant hydrogels have exhibited the desired thermosensitive behaviours: the gelation kinetics at room temperature were slow enough for hours of necessary manipulation of the system in its liquid state, and upon temperature elevation to 37°C, gelation could occur within minutes. Such characteristics of the developed hydrogels demonstrate great potentials for translation into applications at human physiological temperature, including cutaneous wounds. With the high water content percentage in the hydrogel wound dressing, a moist environment is ensured to promote healing. The interconnected pores in the inherent structure of hydrogel matrix have supported its suitability for loading and release of particles. Hydrogel CH1.36:βGP0.267:SHC0.025 with homogenously dispersed CDNs has provenly displayed the features of a monolithic drug delivery system, functioning through diffusional outlet of encapsulated CDNs. The diffusivity of the released CDNs were calculated to be 0.53 μm2s-1 in the hydrogel matrix, about 1⁄4 of that in the suspension conditions, providing evidences on the retention of CDNs by the hydrogel and its control over the CDN release rate. Future works shall be a continuation of the current studies to confirm the cytotoxicity and efficacies of the proposed integrated therapy with appropriate in vitro and in vivo models. As the state-of-art knowledge is yet to address the question how CDNs mediated their curative capabilities, specific protein marker and RNA studies can be performed to explore how properties are preserved by CDNs from their cell sources and thus tune them for targeted applications.